Stability of the Pexider functional equation - Badora, Roman; Przebieracz, Barbara; Volkmann, Peter (Annales Mathematicae Silesianae, 2010)
A stability result for the Pexider equation will be derived from a stability theorem published in [9] for the Cauchy functional equation. Then we discuss the quality of some constants occuring in this context; as a model case we consider functions defined on the multiplicative semigroup 1, 0.